Genetic variability and correlation studies of mulberry (Morus alba L.) genotypes in Bangladesh - Rahman, Md Serajur; Islam, SM Shahinul (Bangladesh Journal of Botany, 2020)
Morphological, phenotypical and yield attributing characteristics of 20 mulberry genotypes were evaluated. Genotypic and phenotypic variations, heritability, genetic advance and correlation co-efficient were also estimated. It was found that the phenotypic co-efficient of variation (PCV) was higher (97.68%) than genotypic co-efficient of variation (GCV, 96.99%). The broad sense heritability for these traits ranged from 98.60 (AL) to 4.69 (LLS). High heritability coupled with high genetic advance was recorded for the characters apex length (AL), leaf length (LL), leaf width (LW), leaf petiole ratio (LPR) and petiole length (PL) suggesting the higher genetic control over these traits. Significant positive correlations to leaf yield/plant were observed for the characters, namely total shoot weight (0.817), longest shoot length (0.600), total branch height (0.596) and leaves fresh weight/10 leaves (0.425). Leaf yield showed significantly positive phenotypic and genotypic correlations with all other growth traits (viz., total shoot weight 0.817, length of longest shoot 0.600, total branch height 0.596 and leaves fresh weight/10 leaves 0.425) except total branch number, nodes per meter, leaf width and petiole length. High genetic advance as percentage of mean coupled with heritability was observed on AL, LL, LW, LPR, PL and 10 fresh leaves weight suggesting the prevalence of additive gene action with low environmental influence for the determination of these characters and could be effective in phenotypic selection. Analysis of variances (ANOVA) for characters such as AL, LL, LW, LPR and PL showed significant variations among the genotypes. Since mulberry is mainly cultivated for leaf yield, genotypes having higher AL, LL, LW and LPR and PL must be given importance during parent selection to evolve high yielding varieties across different seasons in mulberry.